Measurement of hydraulic pressure on the sinus membrane for safer control during transcrestal sinus lifting. Issue 9 (September 2021) - Ro, J.H.; Moon, J.H.; Cheon, M.C.; Park, C.J.
Abstract: The aim of this study was to determine the hydraulic pressures necessary to separate and lift the sinus membrane from the sinus floor in order to ensure a more controlled and safer hydraulic transcrestal sinus lifting surgery and prevent sinus membrane perforation. A flow-regulating hydrodynamic device with a pressure sensor was used in nine patients. The hydraulic pressure was found to increase steadily up to a mean peak of 25.0 ± 13.0 kPa, which is comparable to the medium suction power of ordinary vacuum cleaners. Subsequently, there was a short plateau followed by a sharp decrease in the hydraulic pressure.